Karakteristik Kimia dan Fisik Beras Terserang Kutu (Sitophylus oryzae. sp): Chemical and physical characteristics of Rice Infested with lice (Sitophyllus oryzae. sp) - Juniarti, Rani; Samsu Udayana Nurdin; Siti Nurdjanah; Subeki; Udin Hasanudin (JURNAL AGROINDUSTRI HALAL, 2022)
Rice (Oryza sativa) is susceptible to damage during storage including quantity and quality. Rice during storage for a long time will experience a decrease in quality both chemically and physically. This study was aims to determine the chemical and physical properties of rice attacked by lice (Sitophyllus oryzae sp). The experiment was arranged in a Randomized Completely Block Design (RCBD) with treatments in the form of samples of commercial rice, rice free of lice, rice attacked by lice. and by product of lice-attacted rice. The study consisted of 4 treatments with 6 replications. The data will be statistically tested using the SPSS 25 application. All data are further processed with the Least Significant Difference Test (BNT/LSD) at the 5% level. The chemical properties of rice infested with lice cause an increase in moisture content, lower protein content and total starch content. The physical properties of rice attacked by lice caused a decrease in water absorption, oil absorption and whiteness. The results showed that rice that was attacked by pests with moisture content of 13.23%, crude protein content 4.90%, total starch content 73.82%, water absorption capacity of 2.09 g/g, oil absorption capacity of 1.93 g/g and whiteness of 80.23.